How to induce resistance to the misinformation effect? Characteristics of positive feedback in the reinforced self-affirmation procedure - Szpitalak, Malwina (Psychology, crime & law, 2019)
The memory misinformation effect consists in the inclusion in witness testimonies of information from sources other than the given event. In the present article, research which aims to make people resistant to misinformation is presented. It is based on reinforced self-affirmation (RSA), a method designed to enhance participants’ self-confidence and therefore make them more willing to rely on their own memories instead of external sources. RSA includes self-affirmation and positive feedback. In the present research, the efficacy of various kinds of positive feedback was explored. The results of Experiment 1 suggested that positive feedback relating to memory (MemRSA) is effective in reducing the misinformation effect, while positive feedback relating to general cognitive ability is not. In Experiment 2, the superiority of MemRSA over inefficient feedback relating to attention was demonstrated. In Experiment 3, MemRSA was again effective, and more effective than inducing convictions about the independence of judgements, but this also reduced the misinformation effect. The results are discussed from the perspective of witnesses who remember the correct information yet rely on external sources due to a lack of confidence in t aforementioned heir memories.